Understanding the learning process of french as a second language by identifying the language skills that represent a challenge for the students and the learning strategies they use to succeed - Ulloa López, Rafael Ángel; Chávez Martínez, Ana Sofía; Barahona Muñoz, José Victorino; Vargas Gómez, Laura Goretty; Barahona Muñoz, José Victorino; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2011)
This research begins with the premise that strategies are important if students are to learn effectively, and that this applies not only to language but also to any other field of learning. Therefore this study looks into the strategies used by the students from the Modern Languages Major in language skills development, so they could successfully complete their studies in French. The research used a questionnaire to gather the information to apply the quantitative measurement. Besides, this study identifies the strategy patterns by looking into the effects of some individual factors such as gender, learning style, strategy preference in skills and categories of the strategies implemented. The findings highlight the importance in strategy usage for the development of the learning of French and question its effectiveness through the learning process of the individuals. In addition, implications of the findings for the learning situation are discussed. The patterns of strategy used identified in this study may help instructors get better understanding of Modern Languages students‟ performance. The different strategy choices found in this approach also offer some insights into pedagogical practices that can successfully be employed in the French learning contexts.
The Four language skills -- The Learning styles -- The Learning strategies -- Learning speaking -- Learning listening -- Learning writing -- Learning reading -- Learning styles -- Sensory preferences -- Visual students.
Anexos.
Tesis -- (Licenciatura en Lenguas Modernas opción Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2011
Bibliografía : h. 59-61
Audiencia general
La tesis está en formato digital.
Keywords: Francés -- Enseñanza; Lenguaje y lenguas -- Enseñanza; Técnicas de enseñanza; Adquisición de segundo lenguaje